THE IMPACT OF INTEGRATED REPORTING ON VALUE CREATION FOR SHAREHOLDERS: THE MODERATING EFFECT OF BOARD EFFECTIVENESS: CASE OF SRI LANKA - Roshan, W. Herath (My University, 2018)
Attached

In the today’s business context, more than half the world’s enterprise value is explained by the intangible assets, interestingly more than 70% of these intangibles are not captured by the traditional corporate reporting. Globally, calls for improved corporate reporting were continuing: as a response to this the International Integrated Reporting Council (IIRC) was established in 2010. IR is not just another corporate reporting tool rather it is founded on integrated thinking which focuses value creation. According to the instrumental stakeholder theory, IR which is founded on integrated thinking will lead to the value creation for shareholders by an organization. IR and integrated thinking are decision effect by the board of directors of an organization. However instrumental stakeholder theory, in explaining the value creation by an organization through IR has failed to acknowledge the influence of board of directors on the IR. Therefore, this study is designed to examine the impact of integrated reporting on value creation and how the board effectiveness moderates the relationship between integrated reporting and value creation. The level of integrated reporting is assessed using a check list developed based on the IR Framework. The developed checklist is applied against the integrated reports of all the listed companies in the Colombo Stock Exchange (CSE) who adopt the integrated reporting for the reporting period 2015 to 2018. The level of board effectiveness is assessed using an index developed based on Code of Best Practice on Corporate Governance 2017. The index is applied against the cooperate governance-board of directors section of the integrated reports of all the listed companies in the Colombo Stock Exchange (CSE) who adopt the integrated reporting for the reporting period 2015 to 2018. In this study, it is predicted that the the level of integrated reporting is positively impact the value creation for shareholders and the relationship between the level of integrated reporting and value creation is moderated by the board effectiveness.